NOVEL âGADIS PANTAIâ KARYA PRAMOEDYA ANANTA TOER: ANALISIS STRUKTURAL LÃVI-STRAUSS - Siminto, Siminto (LP2M IAIN Palangka Raya, 2008)
The objective of this study is to make analysis the content of this novel. In analysing of this novel, it used Levi-Strauss Structural Analysis. This novel tries to criticize one of the side Javanese feudalisme that has the uncivilized and inhuman character. Meanwhile, it also tells about the social relationship between the second class that is different in javanese people structure, they are the have class with the poor class. Because of that, by simple writing, it will try to verify the structure of the Beach Girl Novel and structure of javanese people relationship by using the Levi-Strauss Structuralism Approach. For more clear explanation of this novel, keep trying to read of this writing.Â